Lightweight racing shoes improve 5-km running performance, running economy and alter running biomechanics in trained runners - Fuller, J.; Thewlis, D.; Margarita, T.; Brown, N.; Buckley, J. (19th Annual Congress of the European College of Sport Science (ECSS), Amsterdam, 2. - 5. July 2014, 2014)
Introduction: Lightweight footwear is advocated as a means for improving running economy (Moore et al., 2014) but the effect of lightweight footwear on running performance has not been investigated. The purpose of this study was to determine if trained distance runners, unaccustomed to running in lightweight/minimalist footwear and who normally run with a hindfoot strike gait pattern, perform better over a 5-km running distance when wearing a lightweight racing shoe or a standard running shoe. Running economy, vertical oscillation of the centre of mass (COM) and the impulse of the braking shear force were also compared between shoes. Methods: A cross-over study design was used with order of shoes randomized and balanced across participants. Twenty-six trained runners performed a 5-km treadmill time-trial and three 6-min sub-maximal treadmill-running bouts at 11, 13 and 15 km/h in both shoe conditions. Running economy was determined from energy expenditure at each running speed assessed by indirect calorimetry. Vertical oscillation of the COM and the impulse of the braking shear force were calculated from motion capture data and ground reaction forces, which were measured during five overground running trials using a 12 camera VICON MX F20 system and four force platforms aligned in series. Results: In the lightweight racing shoe, runners completed the 5-km time trial faster (Mean difference [MD]=21-s; P<0.01), were more economical running at 11, 13 and 15 km/h (MD=0.92, 1.66 and 2.59 kJ/min, respectively; P<0.01) and ran with less vertical oscillation of the COM (MD=3-mm; P<0.01). Improvements in running economy increased with increasing running speed (P=0.02). The impulse of the braking shear force did not differ between shoe conditions (MD=0.78 Ns; P=0.11). Discussion: Distance runners can improve 5-km running performance through the use of lightweight racing shoes without any prior experience running in lightweight/minimalist footwear. Similar to previous research (Moore et al., 2014), runners ran with improved running economy when using lightweight shoes. Interestingly, improvements in running economy increased with increasing running speed suggesting that lightweight shoes may be most beneficial to runners capable of running at faster race paces. Additionally, a lower vertical oscillation of the COM suggests that runners performed less mechanical work against gravity running in the racing shoe, which could have contributed to the lower metabolic cost.